Characterization of odor active compounds of fresh and dried turmeric by gas chromatography-mass spectrometry, gas chromatography olfactometry and sensory evaluation - Laokuldilok, Natcha; Utama-ang, Niramon; Kopermsub, Phikunthong; Thakeow, Prodpran (Food and Applied Bioscience Journal, 2017)
The volatile compounds of fresh and dried turmeric (Curcuma longa L.) rhizomes were analyzed by gas chromatography-mass spectrometry (GC-MS), gas chromatography-olfactometry (GC-O) and descriptive sensory analysis (DA). It was found that the extract of fresh rhizome is composed of 31 volatile compounds, the majors being guaiacol, alpha-turmerone and vinylguaiacol, whereas, the extract of dried rhizome is composed of 20 volatile compounds, the majors being alpha-turmerone, vinylguaiacol and guaiacol. By GC-O analyses, we identified eleven and six odor active compounds in fresh and dried rhizome extracts, respectively. Bisabolene and vinylguaiacol had high detection frequency and were selected as specific markers related to sensory attributes. Descriptive analysis revealed that the odor of turmeric was described by 3 sensory terms as turmeric, green and heat.